Analisa Perancangan Aplikasi Pendaftaran Siswa Baru Berbasis Website Metode Waterfall (Studi Kasus: SMA Muhammadiyah 07 Sawangan Depok) - Fadlan Fadillah; Ari Syaripudin (CV. Multi Kreasi Media, 2024)
Developing an online new student registration system in schools is expected to make the implementation of new student registration easier and faster and because of that the participants and parents of participants do not have to bother coming to school to just see announcements and or information. relating to the implementation of using the new student registration system. SMA Muhammadiyah 07 Sawangan Depok Sepatan is a private school which currently still uses a manual new student registration system, where prospective students have to come directly to school to register and there are many problems such as writing about new student candidates that cannot be read which causes data errors and missing documents. important documents for student registration at school because they are not well documented. The author examines the new student registration system for SMA Muhammadiyah 07 Sawangan Depok can assist in registering prospective students so that it can be competent, accurate, effective and the data becomes more regular. Muhammadiyah 07 Sawangan Depok High School has also provided database-based data storage which can make it easier for the new student registration committee to assist in preparing information system reports. So that it can make it easier for prospective students to register without having to come to school.